Animal-and mineral-based medicines in Gansu-Ningxia-inner Mongolia region, P.R. China: a cross-cultural ethnobiological assessment - Luo, Chaoqun; Zhao, Wenji; Liu, Sha; Luo, Mingxia; Fan, Tingting; Zhao, Yongxia; Ren, Yan; Wu, Faming; Xie, Jian (Frontiers in Pharmacology, 2023)
Traditional animal-and mineral-based medicines are widely used in the Gansu-Ningxia-Inner Mongolia junction zone, a region with diverse ethnic groups and cultures. This study aims to document, conserve, and explore the potential of these medicines for further research and sustainable development of ethnic medicine. Methods: We interviewed 56 informants from different ethnic backgrounds and analyzed their responses quantitatively. Additionally, a comparative analysis with adjacent regions was conducted, providing invaluable contextual insights.The study unveiled a diverse array of traditional medicines in the Gansu-Ningxia-Inner Mongolia junction zone. A total of 47 animal-based medicines were identified, ranging from insects and scorpios to distinctive animal organs. Of notable significance was Moschus, emerging as a pivotal traditional Chinese medicine resource. In parallel, 12 mineral-based medicines were cataloged, procured both locally and from -pharmacies‖. Female informants, frequently local herbal practitioners, demonstrated broader knowledge of medicines. The analysis of 13 villages revealed varying perceptions of medicine importance, underscoring the wealth of traditional knowledge. Specific medicines, such as Feng-Mi and Xie-Zi, were widely used and valued in local healthcare practices for their cultural and medicinal benefits.This study provides a comprehensive overview of traditional animal-and mineral-based medicines in the Gansu-Ningxia-Inner Mongolia junction zone. It highlights the need for preserving and applying these practices in a sustainable manner. It also lays a solid foundation for future research on ethnic medicine, which can contribute to the holistic well-being of local communities.